Las técnicas de medición por medio de las escalas en la investigación social (2006)
ABSTRACT: WHAT IS A SCALE? Set of items or proposals designed by the investigator according to certain conceptual definitions previous and used to quantify characteristics or variables of the social behavior. These characteristics are conceived generally as "latent" or "not-you declare."